Is it an advantage or disadvantage to usage angiotensin-converting enzyme inhibitor or angiotensin receptor blocker in COVID-19 patients? - Gurlek, Feridun; Tasdemir, Eyyüp (International Journal of Research in Medical Sciences, 2020)
Background: The use of angiotensin converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs) is an important problem for clinicians who treat coronavirus disease (COVID-19) in patients with hypertension. The aim of the study was to reduce the confusion in this matter to some extent. Methods: This study was carried out in the Health Sciences University, Bursa High Specialization Training and Research Hospital between 23 March to 23 June 2020. Patients were evaluated using thorax computed tomography (CT) taken during hospitalization with severity and risk scoring, confusion, uraemia, respiratory rate, blood pressure, age ≥65 years, score >2 (CURB-65) for pneumonia. Results: The rate of severe pneumonia was significantly higher in the group using ACEI and ARBs. CURB 65 high risk observation rate was significantly higher in the group with ACEI and ARB using. The rate of severe pneumonia observed was significantly higher in the any antihypertensive drugs using group. This risk height is more pronounced in those using ACEI and ARBs. The mortality rate of our 500 patients with COVID-19 was 2.2% (11/500). There was no history of hypertension in these 4 patients, but 1 (1/4) of these 4 patients had diabetes. Six patients were taking ACEI and/or ARB in combination with their diuretic, calcium channel blocker and beta blocker. Only one patient was taking calcium channel blocker and beta blocker. Conclusions: The risk of severe pneumonia may increase in COVID-19 positive patients using any antihypertensive drug. It was more pronounced in those using ACEI and ARB. We believe that more comprehensive studies are needed in this about.